Synthesis and luminescence of Sr2SiO4:Eu3+ micro-spherical phosphors by a spray-drying process. (February 2015) - Feng, Hao; Yang, Yang; Zhang, Xiuguo; Xu, Yongchun; Guan, Jinyu
Highlights: The synthesis of Sr2 SiO4 :Eu 3+ dense microspheres by spray-drying process. The influence of heat-treatment temperature on properties of Sr2 SiO4 :Eu 3+ samples. The two sites of Eu 3+ ions in Sr2 SiO4 host. Abstract: We synthesized Sr2 SiO4 :Eu 3+ phosphors with spherical morphology by a spray-drying process. The obtained samples were characterized by XRD, SEM, and spectrophotometer. The XRD results show that samples have good crystallinity after the heat-treatment at 1150 °C. The higher temperature has no obvious influence on the crystallinity and will destroy the spherical morphology. The SEM results show that the phosphors are microspheres with size in the range of 0.8–2.1 μm when they were heat treated at 1050 °C and 1150 °C. The excitation and emission spectra of the samples indicate that Eu 3+ ions doped into Sr2 SiO4 host successfully. The Sr2 SiO4 :Eu 3+ sample heat-treated at 1150 °C has the highest emission intensity and the longest decay times. The results of this work indicate that the optimized heat-treatment temperature should be at 1150 °C for Sr2 SiO4 :Eu 3+ micro-spherical phosphors synthesized by the spray-drying process.